Suppression of Inflammatory Demyelinaton and Axon Degeneration through Inhibiting Kv3 Channels - Jukkola, Peter; Gu, Yuanzheng; Lovett-Racke, Amy E.; Gu, Chen (Frontiers in Molecular Neuroscience, 2017)
The development of neuroprotective and repair strategies for treating progressive multiple sclerosis (MS) requires new insights into axonal injury. 4-aminopyridine (4-AP), a blocker of voltage-gated K+ (Kv) channels, is used in symptomatic treatment of progressive MS, but the underlying mechanism remains unclear. Here we report that deleting Kv3.1—the channel with the highest 4-AP sensitivity—reduces clinical signs in experimental autoimmune encephalomyelitis (EAE), a mouse model for MS. In Kv3.1 knockout (KO) mice, EAE lesions in sensory and motor tracts of spinal cord were markedly reduced, and radial astroglia were activated with increased expression of brain derived neurotrophic factor (BDNF). Kv3.3/Kv3.1 and activated BDNF receptors were upregulated in demyelinating axons in EAE and MS lesions. In spinal cord myelin coculture, BDNF treatment promoted myelination, and neuronal firing via altering channel expression. Therefore, suppressing Kv3.1 alters neural circuit activity, which may enhance BNDF signaling and hence protect axons from inflammatory insults.